Next-generation transgenic mice for optogenetic analysis of neural circuits - Asrican, Brent; Augustine, George J; Berglund, Ken; Chen, Susu; Chow, Nicholas; Deisseroth, Karl; Feng, Guoping; Gloss, Bernd; Hira, Riichiro; Hoffmann, Carolin; Kasai, Haruo; Katarya, Malvika; et al. (Frontiers in Neural Circuits, 2013)
Here we characterize several new lines of transgenic mice useful for optogenetic analysis of brain circuit function. These mice express optogenetic probes, such as enhanced halorhodopsin or several different versions of channelrhodopsins, behind various neuron-specific promoters. These mice permit photoinhibition or photostimulation both in vitro and in vivo. Our results also reveal the important influence of fluorescent tags on optogenetic probe expression and function in transgenic mice.